MO763THE VON WILLEBRAND FACTOR IS A KEY PLAYER IN ARTERIOVENOUS FISTULA MATURATION*. (29th May 2021) - Laboyrie, Suzanne; De Jong, Alwin; De Vries, Margreet; Lalai, Reshma; Martinez, Laisel; Vazquez-Padron, Roberto; Rotmans, Joris
Abstract: Background and Aims: Low arteriovenous fistula (AVF) maturation rate remains a bottleneck in creating a long lasting lifeline to hemodialysis. AVF maturation is determined by the intricate balance between outward remodeling (OR) and formation of intimal hyperplasia (IH), during which vascular smooth muscle cell (VSMC) proliferation is essential. Recently, the von Willebrand Factor (VWF) has been shown to induce VSMC proliferation in vitro and in vivo. In this study we investigate the role of VWF on VSMC proliferation and AVF functionality to gain a better understanding of the relationship between the two latter processes. Method: AVFs were created in wild-type (WT) and VWF (-/-) deficient (B6.129S2-Vwf tm1Wgr) mice using the external jugular vein and the common carotid artery (CCA). Mean velocity and diameter of the CCA was measured at baseline before surgery, t=0 immediately post-surgery, t=7 and t=14 using ultrasonography to determine flow volume (mL/s). The mice were sacrificed at t=14, AVFs were collected and OR and IH were analyzed using Weigert's elastin and aSMA staining, using the Mann-Whitney test. To study VSMC proliferation in vitro, VSMCs were isolated from vena cava explants. VSMCs from VWF -/- mice were cultured with 10% VWF -/- plasma with or without addition of VWF (Wilfactin). Proliferation was measured after 40 hours. Humane patient-matched samples were obtained during two stage brachio-basalic AVF surgery: the native veins at creation and venous AVF samples at transposition. Maturation was defined as a luminal AVF diameter of > 6 mm. Samples were stained for VWF and aSMA. Positively stained tissue in the medial layer was quantified using Histoquant and analyzed with the Wilcoxon signed-rank test. Results: WT mice showed better outcomes in AVF functionality. Whereas blood flow did not increase in VWF deficient mice over two weeks after AVF-creation, WT mice showed a steady increase in flow rate from t=0 to t=7 (1.97 fold) and t=14 (3.0 fold) . At 14 days, VWF -/- mice showed significantly reduced OR compared to WT mice, with a 1.46 fold smaller venous perimeter (p=0.008). Formation of IH was also significantly reduced in VWF -/- mice (9.58 fold change, p = 0, 0001), with a non-significant 1.42 fold difference in luminal area. Lastly, an 8.05 fold decrease was observed in aSMA+ cells in the IH of VWF -/-mice (p = 0.0002). In vitro, addition of VWF caused an 1.5 fold increase in proliferation compared to VWF deficient VSMCs cultured without VWF (p=0.016). As for chronic kidney disease (CKD) patients, our study showed significant wall thickening and increase in aSMA+ tissue only in matured AVFs. There was significant upregulation of VWF+ tissue in the media from native veins to venous AVF samples, with 183% in failed AVFs (p= 0.026) and 425% in matured AVFs (p= 0.013). Matured AVFs had a 4.6 fold increase in VWF+ area in the medial layer compared to failed AVFs (p= 0.033). Conclusion: Our study demonstrates VWF as an inducer of VSMC proliferation and thereby both OR and IH. Secondly, we show that VWF is essential for AVF maturation and that enhanced expression in the media coincides with AVF maturation in CKD patients.